Fear of failure dengan ketidakjujuran akademik pada siswa SMA yang menjalankan sistem kredit semester - Najah Hamzah Bauzir; Uun Zulfiana (Cognicia, 2021)
The duration of study for Credit Semester System or Sistem Kredit Semester (SKS) students is 2 years at the earliest and 4 years at the longest. This condition can cause students to commit academic dishonesty for fear of failing to get good scores. The purpose of this study was to determine the relationship between fear of failure and academic dishonesty in high school students who run in the SKS format using correlational quantitative research methods. The sampling technique was purposive sampling. The research subjects are high school students who run the SKS for at least 1 year and the numbers are 186 subjects. The data collection method used a modified scale and a combination of the Academic Dishonesty Scale and the Academic Dishonesty Instrument and the Performance Failure Appraisal Inventory (PFAI) scale. The results of the data analysis test using the Pearson product moment method showed that there is no relationship between fear of failure and academic dishonesty in high school students who run the SKS. The correlation coefficient is 0.99 and the significance is 0.178 (p > 0.05).   Keywords: Academic dishonesty, fear of failure, high school students running the SKS